(untitled) (Diversity Research: Journal of Analysis and Trends, 2026)
This article examines the principles for constructing an electronic linguistic database of translation units derived from literary texts within the framework of corpus linguistics in Turkology. It elucidates the role of parallel corpora in the analysis of translation processes and in the identification of linguistic features across Turkic languages. The study delineates the principal stages of database development, including data collection, preprocessing, alignment, annotation, and system implementation. Particular emphasis is placed on the capabilities of Uzbekcorpus.uz as a significant resource for the study of literary texts and translation units. The findings indicate that such databases contribute to the improvement of translation quality, facilitate in-depth linguistic analysis, and promote the advancement of corpus-based research in Turkology